Effects of intravenous lipopolysaccharide administration on feed intake, ruminal forage degradability, and liquid parameters and physiological responses in beef cattle - Lippolis, K. D. (2017)
This experiment compared DMI, ruminal forage degradability, and liquid parameters as well as physiological responses in beef cattle receiving a lipopolysaccharide (LPS) challenge or not. Eight ruminally cannulated Angus × Hereford steers (485 ± 16 kg BW) were housed in individual pens on d −7, ranked by BW, and allocated to 1 of 2 treatments administered on d 0: 1) an intravenous (i.v.) bolus dose (0.5 μg/kg of BW, diluted in 5 mL of 0.9% sterile saline) of bacterial LPS (Escherichia coli 0111:B4) or 2) a 5-mL i.v. injection of 0.9% sterile saline (CON). Steers had free-choice access to mixed alfalfa–grass hay, water, and a commercial vitamin + mineral mix during the experiment (d −7 to 6). Hay DMI was evaluated daily from d −5 to 6. Immediately prior to treatment administration (h 0), polyester bags containing 4 g of ground dietary hay (DM basis) were immersed into the rumen of each steer and incubated for 0, 4, 8, 12, 24, 36, and 48 h for DM and NDF degradability evaluation. Steers were also intraruminally pulse-dosed with 5 g of Co-EDTA immediately prior to treatment administration, and rumen fluid samples were collected at 0, 2, 4, 6, 8, 12, 16, and 24 h for ruminal liquid volume and dilution rate calculations. Blood was collected every 2 h from −2 to 8 h, every 4 h from 8 to 16 h, every 12 h from 24 to 72 h, and every 24 h from 96 to 144 h relative to treatment administration. Values obtained before treatment administration were used as a covariate within each respective analysis. Steers receiving LPS had less (P ≤ 0.03) DMI on d 0 and 1 compared with CON steers. Steers receiving LPS had reduced (P ≤ 0.05) rumen liquid volume and dilution rate as well as ruminal disappearance rate and effective degradability of DM and NDF compared with CON steers. Steers receiving LPS had greater (P ≤ 0.05) plasma tumor necrosis factor α at 2 h, greater plasma hapto-globin from 24 to 72 h, greater plasma cortisol from 12 to 16 h, greater serum NEFA from 6 to 48 h, greater plasma insulin and glucose at 2 h, reduced plasma glucose from 4 to 12 h, greater plasma cholecystokinin at 16 h, and greater plasma leptin concentrations at 8, 12, 16, 36, 48, and 60 h after treatment administration compared with CON steers. Hence, LPS administration transiently reduced DMI in steers via physiological reactions that modulate gastrointestinal motility and satiety centers in the central nervous system, in addition to potential host–microbiome endocrine interactions that impaired ruminal hay DM and NDF degradability.